A Comparison Study On Reading Comprehension Between Male And Female Students - Hildayanti Witri; M. Fauzan Ansyari (Journal of Pedagogy and Online Learning, 2022)
This study was aimed at finding out the difference on reading comprehension between male and female students at the eleventh grade of State Senior High School 1 Bangkinang Kota. The research design was proactive ex post facto research. The population and sample was the eleventh social science students. The number of sampling was selected by using stratified disproportional technique. Inferential analysis “Independent Sample T-Test” technique was used to measure the difference on reading comprehension between male and female students and descriptive analysis was used to know the dominant factors that influence reading comprehension for male and female students. Based on the research findings, it was found mean score of male students was 61.87 and were categorized into enough level, then female students was 70.13 and were categorized into good level. Moreover, the sig was 0.012 < a (0.05). Therefore, it could be concluded that Ho was rejected and Ha was accepted, it means there is a significant difference on reading comprehension between male and female students at the eleventh social science class of State Senior High School 1 Bangkinang Kota. Whereas, the factors for male students were social environment (22.8%), talent (21.2%), background knowledge (20.6%), vocabulary (19.6%), and motivation (15.8%). While the factors for female students were motivation (22.2%), social environment (20.9%), background knowledge (20.5%), talent (18.6%), and vocabulary (17.8%).